Dangerous crooked scoundrels : insulting the president, from Washington to Trump - Battistella, Edwin L. (b)
History of insults aimed at United States presidents, from George Washington to Donald Trump.
Includes bibliographical references and index.
Keywords: Presidents -- United States; Invective -- History; Political cartoons -- History